1986
DOI: 10.1007/bf00508431
|View full text |Cite
|
Sign up to set email alerts
|

Amylase in human lungs and the female genital tract

Abstract: We investigated the localization of amylase in normal human lungs and the female genital tract using immunohistochemical and histochemical methods. Immunohistochemical procedures were applied to formaldehyde-fixed, paraffin-embedded specimens as well as to cryostat sections of periodate/lysine/paraformaldehyde (PLP)-fixed tissues. The starch-substrate-film method was used for the histochemical investigation of unfixed frozen sections. Amylase immunoreactivity was observed in ciliated epithelial cells of the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The highly corrosive environment of the human body restricts the materials to be used for implants [2]. High corrosion resistance is required for the material to use in this corrosive environment [3]. Moreover, wear debris produced from movement of joints can lead to wearcorrosion causing biodegradation [4].…”
Section: Introductionmentioning
confidence: 99%
“…The highly corrosive environment of the human body restricts the materials to be used for implants [2]. High corrosion resistance is required for the material to use in this corrosive environment [3]. Moreover, wear debris produced from movement of joints can lead to wearcorrosion causing biodegradation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, enzyme amylase (AMY2B) plays a major role in converting glycogen into sugar. Several studies indicated that there is an upregulation of AMY2B in the human Fallopian tube (Mc et al 1958, Hochberg 1974, Hayashi et al 1986, Groot et al 1990, Marquez et al 2005. Therefore, it is likely that the compact polysaccharide can be converted into a simple sugar by AMY2B in the oviduct, and these simple sugar molecules can be used in cellular metabolism by both the oviduct and the cleaving embryo.…”
Section: Nutrientsmentioning
confidence: 99%
“…A low level of transcripts, -1 % of the level in the parotid gland, was present in lung and in samples containing ovary and oviduct. Salivary amylase has been detected in h u m a n lung and ovarian tumors (Hayashi et al 1986). …”
Section: Expression Of Human Growth Hormone Fusion Genesmentioning
confidence: 99%